Three-layer functionalized anode and its application in high-power energy storage battery

CN122696635BActive Publication Date: 2026-11-03ZHEJIANG BAIMA LAKE LABORATORY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611183997.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-11-03
Estimated Expiration
2046-08-06

AI Technical Summary

Technical Problem

Existing high-power energy storage batteries have problems with high internal resistance, poor rate performance and cycle life under high areal loading, as well as insufficient safety and stability. This is mainly due to the difference in reaction rates between the electrolyte side and the current collector side, which leads to ion channel congestion and local polarization hotspots.

Method used

A three-layer functionalized anode structure is adopted, including a conductive-working ion nucleation layer, a high-capacity fast lithium storage layer, and an ion flux regulation-stabilized SEI layer. Through the functional partitioning design and porosity control of the material, the electron and ion transport paths are optimized, the internal resistance is reduced, and the battery performance is improved.

Benefits of technology

Significantly reduces the internal resistance of lithium/sodium-ion batteries, improves rate performance, cycle life and safety stability, and meets the needs of high-power energy storage batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122696635B_ABST
    Figure CN122696635B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of battery negative electrodes, and discloses a three-layer functionalized negative electrode and application of the three-layer functionalized negative electrode in high-power energy storage batteries. The three-layer functionalized negative electrode comprises a current collector, and a bottom layer, an intermediate layer and a surface layer are arranged on the current collector layer by layer; the bottom layer contains conductive carbon material and working ion nucleating agent; the intermediate layer contains carbon-based lithium storage material; and the surface layer contains porous carbon material, solid-state fast ion conductor and solid electrolyte interface film precursor. In the negative electrode, a functional partition structure of 'conductive-working ion nucleating layer -> high-capacity fast lithium storage layer -> ion flux regulation-stable SEI layer' is constructed along the thickness direction, the internal resistance of the energy storage battery can be reduced to a greater extent, and the rate performance, cycle life and safety stability of the energy storage battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery anode technology, and in particular to a three-layer functionalized anode and its application in high-power energy storage batteries. Background Technology

[0002] With the rapid development of energy storage scenarios such as renewable energy grid connection and grid-side frequency regulation, higher requirements are placed on the comprehensive performance of lithium-ion batteries and sodium-ion batteries: high energy density is required to reduce system costs, high power density is required to meet the needs of frequent charging and discharging, and excellent safety and ultra-long cycle life must be guaranteed.

[0003] Existing high-rate anodes typically reduce transmission impedance by thinning the electrode, increasing the content of conductive agents, using small-particle-size graphite / hard carbon, or adding silicon-carbon materials. However, thinning the electrode sacrifices areal capacity and volumetric energy density; excessive conductive agents and binders dilute the active material; small-particle-size materials have a high specific surface area, which easily leads to the formation of thicker interfacial films; and silicon-carbon materials suffer from volume changes, contact failures, and interfacial film instability during high-rate cycling.

[0004] In the design of existing high-power energy storage cells, reducing internal resistance through the synergy of cell structure, electrode materials, and processes is an important direction. However, traditional single-layer or simple hybrid anodes (such as patent CN122000333A) improve anode performance by incorporating functional materials, but still mainly rely on the structure formed by random particle stacking. Their interfacial film formation and electron and ion channels are difficult to achieve simultaneously at their optimal state. Especially in high areal loading anodes, the reaction rates on the electrolyte side and the current collector side differ significantly, easily leading to problems such as ion channel front-end congestion, insufficient utilization of inner-layer active materials, and localized polarization hotspots. This results in high internal resistance, poor rate performance, cycle life, and safety stability. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a three-layer functionalized negative electrode and its application in high-power energy storage batteries. The negative electrode of this invention incorporates a functional partitioning structure along its thickness direction: a conductive-working ion nucleation layer → a high-capacity, fast lithium storage layer → an ion flux regulation-stabilized SEI layer. This structure can significantly reduce the internal resistance of lithium / sodium-ion batteries and improve their rate performance, cycle life, and safety stability, thus better meeting the application requirements in high-power energy storage batteries.

[0006] The specific technical solution of this invention is as follows: In a first aspect, the present invention provides a three-layer functionalized negative electrode, comprising a current collector, wherein the current collector is provided with a bottom layer, an intermediate layer and a top layer in succession; the bottom layer contains a conductive carbon material and a working ion nucleating agent; the intermediate layer contains a carbon-based lithium storage material; and the top layer contains a porous carbon material, a solid fast ion conductor and a solid electrolyte interphase (SEI) membrane precursor.

[0007] In the negative electrode structure of this invention, the bottom layer, the intermediate layer, and the top layer can respectively perform the following functions: (1) The bottom layer in contact with the current collector contains conductive carbon material and working ion nucleating agent, which can give the layer good conductivity and promote the nucleation ability of working ions (when the negative electrode is used in sodium-ion battery, the "working ion" is sodium ion; when the negative electrode is used in lithium-ion battery, the "working ion" is lithium ion). With the bottom layer having the above characteristics, the electron transport backbone can be moved forward to the surface of the current collector and the working ions can be uniformly nucleated near the current collector side, which can reduce the difference in in-plane current distribution, suppress local lithium / sodium plating on the current collector side and increase contact resistance.

[0008] (2) The intermediate layer contains carbon-based lithium storage material, which enables the layer to perform high-capacity rapid lithium / sodium storage in the negative electrode and obtain high power output without significantly reducing the areal capacity.

[0009] (3) The surface layer is located on the side close to the separator in the battery. The porous carbon material enables the layer to buffer and homogenize the ion flow entering the negative electrode. At the same time, the solid fast ion conductor and SEI film precursor help to form a stable interface on the negative electrode surface, which can reduce the repeated rupture of the SEI film, the generation of dead lithium / dead sodium and high-temperature side reactions.

[0010] Through the above method, this invention constructs a functional partition structure along the thickness direction in the negative electrode, consisting of a "conductive-working ion nucleation layer → high-capacity fast lithium storage layer → ion flux regulation-stabilized SEI layer," enabling spatial synergy between electron transport, ion transport, interface film formation, and stress buffering. Compared to conventional single-layer negative electrodes and simple hybrid negative electrodes, the specific functional partition design in this invention can significantly reduce battery internal resistance and pulse polarization, thereby improving battery rate performance, cycle life, and safety stability.

[0011] Preferably, the three-layer functionalized negative electrode is the negative electrode of a lithium-ion battery, wherein: In the underlying layer, the conductive carbon material includes one-dimensional and / or two-dimensional carbon materials, and the working ion nucleating agent includes one or more of Ag, Sn, Zn, Mg, Al, ZnO, SnO2, TiN, Li3N, LiF, LiAlO2 and Li-Zn alloy precursors; The intermediate layer contains carbon-based lithium storage materials including one or more of graphite, hard carbon, soft carbon, carbon nanotubes, conductive carbon black, lithium titanate, silicon-carbon composite materials, and silicon-oxygen-carbon composite materials. In the surface layer, the solid-state fast ion conductors include lithium lanthanum zirconium oxide (LLZO), lithium titanium aluminum phosphate (LLZO), lithium aluminum germanium phosphate (LAGP), and tantalum-doped lithium lanthanum zirconium oxide (Li). 6.4 La3Zr 1.4 Ta 0.6 O 12 One or more of the following (LLZTO), the solid electrolyte interface membrane precursor includes one or more of LiF, Li3PO4, LiNO3, lithium dioxolane-borate (LiBOB), lithium difluorooxolane-borate (LiDFOB) and polymer lithium salt complexes.

[0012] Preferably, the three-layer functionalized negative electrode is the negative electrode of a sodium-ion battery, wherein: In the underlying layer, the conductive carbon material includes one-dimensional and / or two-dimensional carbon materials, and the working ion nucleating agent includes one or more of Ag, Sn, Zn, Mg, Al, ZnO, SnO2, TiN, Na3N, NaF, NaAlO2, and Na-Zn alloy precursors; The intermediate layer contains carbon-based lithium storage materials including one or more of graphite, hard carbon, soft carbon, carbon nanotubes, conductive carbon black, lithium titanate, silicon-carbon composite materials, and silicon-oxygen-carbon composite materials. In the surface layer, the solid fast ion conductor includes one or more of sodium superion conductor (NASICON), Na3PS4, Na3SbS4 and β-alumina, and the solid electrolyte interface membrane precursor includes one or more of NaF, Na3PO4, NaNO3, borate film-forming additives and polymer sodium salt complexes; the borate film-forming additives include sodium dioxalate borate (NaBOB) and / or sodium difluorooxalate borate (NaDFOB).

[0013] Preferably, in the bottom layer, the mass ratio between the conductive carbon material and the working ion nucleating agent is 55~85:15~40; and in the top layer, the mass ratio between the porous carbon material, the solid fast ion conductor, and the solid electrolyte interface film precursor is 40~70:10~30:5~20.

[0014] Preferably, the three-layer functionalized negative electrode is a lithium-ion battery negative electrode, wherein: the bottom layer contains carbon nanotubes, reduced graphene oxide, ZnO and LiF; the middle layer contains graphite, hard carbon, silicon-carbon composite material and carbon nanotubes; and the surface layer contains porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF and Li3PO4.

[0015] Preferably, the three-layer functionalized negative electrode is a sodium-ion battery negative electrode, wherein: the bottom layer contains carbon nanotubes, reduced graphene oxide, Sn and ZnO; the middle layer contains hard carbon, soft carbon and conductive carbon black; and the surface layer contains porous hard carbon, sodium superionic conductor and NaF, and contains Na3PO4 and / or borate film-forming additives.

[0016] When the aforementioned materials are selected for the bottom, middle, and top layers, the synergy between different materials within each layer and the overall synergy among the three layers can further enhance the negative electrode's ability to transport electrons and ions, and reduce the battery's internal resistance. Specifically: (1) In the bottom layer of lithium-ion batteries, carbon nanotubes can provide longitudinal electron bridges, reduced graphene oxide can provide in-plane π electron spreading surfaces, ZnO can form polar nucleation sites containing Li-Zn-O during the first lithium insertion process, and LiF can form a highly mechanically stable point-like interface framework at the interface between the bottom layer and the intermediate layer. The carbon nanotubes and reduced graphene oxide in the bottom layer can form a quasi-continuous electronic equipotential surface with a scale between nanowires and sheets at the interface between the bottom layer and the intermediate layer. After ZnO and LiF are distributed on the equipotential surface, depending on the conductive network, polar sites and the matching of particle contact curvature between the two layers, the local lithium insertion reaction near the current collector side of the intermediate layer can be transformed from point-like nucleation to strip-like or planar nucleation, thereby improving the interface bonding between the bottom layer and the intermediate layer and improving the transport stability at the interface. When used in sodium-ion batteries, ZnO can still serve as a polar nucleation adjustment point, while Sn can replace LiF to provide sodium-loving alloying sites. This allows the aforementioned role of "quasi-continuous electronic equipotential surface - polar nucleation site" to be transferred from the lithium intercalation system to the sodium intercalation system. In addition, Sn can undergo an alloying reaction with Na to form sodium-loving sites, reducing the local nucleation energy barrier. This is beneficial for expanding the local point-like sodium storage / nucleation reaction into a more uniform planar or strip-like reaction. Therefore, this invention preferably uses Sn instead of NaF in sodium-ion batteries. In lithium-ion batteries, LiF has better stability at high power, so this invention preferably uses LiF instead of Sn in lithium-ion batteries.

[0017] (2) In the intermediate layer used in lithium-ion batteries, graphite can provide low potential and high reversible capacity, silicon-carbon can provide capacity gain, hard carbon can fill the curvature gaps between graphite flake particles and form a wider lithium-ion inlet, and carbon nanotubes can penetrate the thickness direction of the intermediate layer and overlap with the bottom carbon nanotube-reduced graphene oxide network, thereby reducing the interlayer electronic contact resistance. The combination of the above materials allows electron transport from the bottom layer to the intermediate layer not to simply pass through the interface vertically, but to be repeatedly diverted along the graphite flakes, hard carbon, silicon-carbon composite material and carbon nanotubes, thereby improving the electron transport efficiency and stability at the interface, reducing polarization hotspots caused by local current congestion, and making the utilization rate of active particles near the current collector side of the intermediate layer more uniform. At the same time, the abundant defect sites on the surface of hard carbon in the intermediate layer can generate higher wetting affinity with LiF and Li3PO4 in the surface layer. Through the above mechanism, the hard carbon in the intermediate layer can connect the bottom electron transport network and the surface ion transport network in the intermediate layer through the curved pore walls, so that the intermediate layer has the functions of both an energy storage layer and an interlayer channel conversion layer. When used in sodium-ion batteries, the intermediate layer is preferably composed of hard carbon and soft carbon, utilizing the defect sites of hard carbon and the continuous conductive phase of soft carbon to achieve the synergy between sodium storage sites and electron shunting paths.

[0018] (3) When used in lithium-ion batteries, the surface layer uses porous hard carbon, LLZTO, LiF, and Li3PO4. This allows for the construction of a three-phase parallel ion inlet channel at the interface between the surface layer and the intermediate layer, consisting of "liquid phase pores - solid phase ion conductor - SEI precursor". Specifically, a short-range amorphous phosphate transition layer may be formed between the Li-O framework on the LLZTO surface and Li3PO4, while LiF restricts electron leakage and inhibits further electrolyte decomposition. The porous hard carbon pore walls have similar surface energies to the hard carbon and silicon-carbon composite materials in the intermediate layer, which helps to prevent interface debonding between the intermediate layer and the surface layer. Through these effects, the surface layer can pre-construct an ion channel inlet distributor on the surface of the intermediate layer, which helps to improve the ion transport efficiency within the intermediate layer. When used in sodium-ion batteries, to achieve the same or similar ion inlet distribution effect, it is preferable to replace LLZTO with NASICON, and to replace LiF and Li3PO4 with NaF and Na3PO4 respectively, or to use NaF in combination with borate film-forming additives. NaF can reduce electron leakage and improve the mechanical stability of the SEI in the sodium system, while Na3PO4 or borate film-forming additives can provide an inorganic / organic composite interface with sodium ion affinity, thereby improving the flux homogenization ability of sodium ions at the surface-intermediate layer interface.

[0019] Preferably, the three-layer functionalized negative electrode is a lithium-ion battery negative electrode, wherein: in the bottom layer, the mass ratio of carbon nanotubes, reduced graphene oxide, ZnO and LiF is 40~55:15~30:10~20:5~15; in the middle layer, the mass ratio of graphite, hard carbon, silicon-carbon composite material and carbon nanotubes is 78~92:5~14:3~8:0.2~1.0; in the top layer, the mass ratio of porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF and Li3PO4 is 45~70:10~30:2.5~10:2.5~10.

[0020] Preferably, the three-layer functionalized negative electrode is the negative electrode of a sodium-ion battery, wherein: in the bottom layer, the mass ratio of carbon nanotubes, reduced graphene oxide, Sn, and ZnO is 40~55:15~30:5~15:10~20; in the middle layer, the mass ratio of hard carbon, soft carbon, and conductive carbon black is 80~90:5~10:1~3; and in the surface layer, the mass ratio of porous hard carbon, sodium superionic conductor, NaF, and Na3PO4 is 45~70:10~30:2.5~10:2.5~10 or the mass ratio of porous hard carbon, sodium superionic conductor, NaF, and borate film-forming additive is 45~70:10~30:2.5~10:2.5~10.

[0021] Preferably, the bottom layer, intermediate layer and top layer further contain an adhesive; the adhesive in the top layer includes an elastic adhesive.

[0022] Some carbon-based lithium storage materials in the intermediate layer may undergo reversible expansion during battery cycling. By using an elastic binder on the surface, it is beneficial to prevent local particle debonding, pore collapse and fresh surface exposure caused by expansion stress.

[0023] Preferably, the bottom layer has a porosity of 5% to 30% and an average pore size of 20 to 300 nm; the middle layer has a porosity of 18% to 38% and an average pore size of 0.05 to 1.5 μm; and the surface layer has a porosity of 28% to 55% and an average pore size of 0.1 to 3.0 μm.

[0024] When the porosity and average pore size of the surface layer are too small, electrolyte wetting and ion diffusion are hindered, and concentration polarization increases under high-rate conditions, leading to poor rate and cycle performance of the battery. When the porosity and average pore size of the surface layer are too large, ions can easily pass through the surface layer to reach the intermediate layer surface, making it difficult to be uniformly distributed within the surface layer. Simultaneously, excessively large pore sizes can introduce gas bubbles and metastable states caused by lean electrolyte retention. Trace amounts of gas generated during high-power cycling or high-temperature storage are more likely to be retained and merged within the large pores, forming localized insulating gas plugs. Liquid phase pathways near these gas plugs are forced to flow around them, further leading to uneven ion flux and thus affecting the battery's ion transport performance. This invention controls the surface porosity to 28%–55% and the average pore size to 0.1–3.0 μm, enabling the layer to have good electrolyte wetting and ion diffusion performance, while also providing a good homogenization effect on the ion flow entering the negative electrode. This results in a battery with lower internal resistance and better rate and cycle performance.

[0025] Furthermore, when the three layers are designed with a bottom layer containing carbon nanotubes, reduced graphene oxide, ZnO, and LiF, a middle layer containing graphite, hard carbon, silicon-carbon composites, and carbon nanotubes, and a top layer containing porous hard carbon, LLZTO, LiF, and Li3PO4, the aforementioned porosity and average pore size design of the three layers can also produce the following effects: the nanoscale pore structure formed by the carbon nanotubes, reduced graphene oxide, ZnO, and LiF composites in the bottom layer is suitable for mechanical interlocking with the graphite, hard carbon, and silicon-carbon composites in the middle layer; the curved pore walls generated by the hard carbon in the middle layer are suitable for receiving the ion inlets formed by the porous hard carbon, LLZTO, LiF, and Li3PO4 composites in the top layer; and the matching of porosity and average pore size between the middle layer and the top layer can reduce liquid phase concentration polarization at high magnification; the composite interface of LiF-Li3PO4 and LLZTO in the top layer is suitable for forming continuous but not excessively interconnected ion channels in the range of 0.1~3.0 μm average pore size. By matching the aforementioned materials with porosity and average pore size, the internal resistance, rate performance, and cycle performance of the battery can be further improved.

[0026] More preferably, the porosity of the bottom layer is 8%~20%, and the average pore size is 40~150 nm; the porosity of the middle layer is 22%~32%, and the average pore size is 0.1~0.8 μm; and the porosity of the surface layer is 35%~48%, and the average pore size is 0.2~1.2 μm.

[0027] Preferably, the thickness of the bottom layer is 0.5~5 μm, the thickness of the middle layer is 15~120 μm, the thickness of the top layer is 1~25 μm, and the total thickness of the bottom layer, middle layer and top layer is 20~150 μm.

[0028] More preferably, the thickness of the bottom layer is 1~3 μm, the thickness of the middle layer is 35~85 μm, the thickness of the top layer is 3~15 μm, and the total thickness of the bottom layer, middle layer and top layer is 45~105 μm.

[0029] Secondly, the present invention provides the application of the three-layer functionalized negative electrode in a high-power energy storage battery, wherein the high-power energy storage battery is a lithium-ion battery or a sodium-ion battery.

[0030] Preferably, the high-power energy storage battery includes a positive electrode, a separator, an electrolyte, and the three-layer functionalized negative electrode; the separator is stacked on the surface layer of the three-layer functionalized negative electrode.

[0031] Compared with the prior art, the present invention has the following advantages: (1) In the negative electrode of the present invention, a functional partition structure of “conductive-working ion nucleation layer → high-capacity fast lithium storage layer → ion flux regulation-stable SEI layer” is constructed along the thickness direction. This specific functional partition design can reduce the internal resistance and pulse polarization of lithium / sodium ion batteries to a greater extent, and improve their rate performance, cycle life and safety stability.

[0032] (2) In the negative electrode of the present invention, by selecting carbon nanotubes, reduced graphene oxide, ZnO and LiF in the bottom layer, graphite, hard carbon, silicon carbon composite material and carbon nanotubes in the middle layer, and porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF and Li3PO4 in the surface layer, the coordination between different materials in each layer and the mutual coordination between the three layers can be utilized to further improve the electron and ion transport capability of the negative electrode and reduce the internal resistance of the lithium-ion battery.

[0033] (3) In the negative electrode of the present invention, by selecting carbon nanotubes, reduced graphene oxide, Sn and ZnO in the bottom layer, hard carbon, soft carbon and conductive carbon in the middle layer, and porous hard carbon, sodium superion conductor and NaF and Na3PO4 and / or borate film-forming additives in the surface layer, the cooperation between different materials in each layer and the cooperation between the three layers can be utilized to further improve the electron and ion transport capability of the negative electrode and reduce the internal resistance of sodium ion battery.

[0034] (4) In the negative electrode of the present invention, by controlling the porosity and average pore size of the bottom layer, the middle layer and the surface layer within a specific range and matching them with specific materials in the three layers, the interlayer cooperation effect can be improved, and the internal resistance, rate performance and cycle performance of the battery can be improved to a greater extent. Attached Figure Description

[0035] Figure 1 This is a schematic diagram of one structure of the three-layer functionalized negative electrode in this invention.

[0036] Figure 2 This is a sample photograph of the three-layer functionalized negative electrode of the present invention.

[0037] Figure 3 This is a schematic comparison of the voltage response of Example 1 and Comparative Example 1 under 5C pulse discharge.

[0038] Figure 4 This is a schematic comparison of the capacity retention rates of Example 1 and Comparative Example 1 under 3C / 3C high-rate cycling.

[0039] The attached diagram is labeled as follows: current collector 1, bottom layer 2, intermediate layer 3, and surface layer 4. Detailed Implementation

[0040] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0041] First, the present invention relates to a three-layer functionalized negative electrode, comprising a current collector, wherein the current collector is provided with a bottom layer, an intermediate layer and a top layer in succession; the bottom layer contains a conductive carbon material and a working ion nucleating agent; the intermediate layer contains a carbon-based lithium storage material; and the top layer contains a porous carbon material, a solid fast ion conductor and a solid electrolyte interphase (SEI) membrane precursor.

[0042] In some specific embodiments, the mass ratio between the conductive carbon material and the working ion nucleating agent in the bottom layer is 55~85:15~40.

[0043] In some specific embodiments, the mass ratio of the porous carbon material, the solid fast ion conductor, and the solid electrolyte interface membrane precursor in the surface layer is 40~70:10~30:5~20.

[0044] In some specific embodiments, the three-layer functionalized negative electrode is the negative electrode of a lithium-ion battery, wherein: in the bottom layer, the conductive carbon material includes one-dimensional and / or two-dimensional carbon materials, and the working ion nucleating agent includes one or more of Ag, Sn, Zn, Mg, Al, ZnO, SnO2, TiN, Li3N, LiF, LiAlO2, and Li-Zn alloy precursors; in the middle layer, the carbon-based lithium storage material includes one or more of graphite, hard carbon, soft carbon, carbon nanotubes, conductive carbon black, lithium titanate, silicon-carbon composite material, and silicon-oxygen-carbon composite material; in the surface layer, the solid fast ion conductor includes one or more of lithium lanthanum zirconium oxide, lithium titanium aluminum phosphate, lithium aluminum germanium phosphate, and tantalum-doped lithium lanthanum zirconium oxide, and the solid electrolyte interface film precursor includes one or more of LiF, Li3PO4, LiNO3, lithium dioxolane borate, lithium difluorooxolane borate, and polymer lithium salt composites.

[0045] In some other specific embodiments, the three-layer functionalized negative electrode is the negative electrode of a sodium-ion battery, wherein: in the bottom layer, the conductive carbon material includes one-dimensional and / or two-dimensional carbon materials, and the working ion nucleating agent includes one or more of Ag, Sn, Zn, Mg, Al, ZnO, SnO2, TiN, Na3N, NaF, NaAlO2, and Na-Zn alloy precursors; in the middle layer, the carbon-based lithium storage material includes one or more of graphite, hard carbon, soft carbon, carbon nanotubes, conductive carbon black, lithium titanate, silicon-carbon composite materials, and silicon-oxygen-carbon composite materials; in the surface layer, the solid fast ion conductor includes one or more of sodium superion conductor, Na3PS4, Na3SbS4, and β-alumina, and the solid electrolyte interface film precursor includes one or more of NaF, Na3PO4, NaNO3, borate film-forming additives, and polymer sodium salt complexes; the borate film-forming additives include sodium dioxalate borate and / or sodium difluorooxalate borate.

[0046] In some specific embodiments, the three-layer functionalized negative electrode is a lithium-ion battery negative electrode, wherein: the bottom layer contains carbon nanotubes, reduced graphene oxide, ZnO, and LiF; the middle layer contains graphite, hard carbon, silicon-carbon composite material, and carbon nanotubes; and the surface layer contains porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF, and Li3PO4. Optionally or preferably: in the bottom layer, the mass ratio of carbon nanotubes, reduced graphene oxide, ZnO, and LiF is 40~55:15~30:10~20:5~15; in the middle layer, the mass ratio of graphite, hard carbon, silicon-carbon composite material, and carbon nanotubes is 78~92:5~14:3~8:0.2~1.0; and in the surface layer, the mass ratio of porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF, and Li3PO4 is 45~70:10~30:2.5~10:2.5~10.

[0047] In some other embodiments, the three-layer functionalized negative electrode is a sodium-ion battery negative electrode, wherein: the bottom layer contains carbon nanotubes, reduced graphene oxide, Sn and ZnO; the middle layer contains hard carbon, soft carbon and conductive carbon black; and the surface layer contains porous hard carbon, sodium superionic conductor and NaF, and contains Na3PO4 and / or borate film-forming additives. Optionally or preferably, the mass ratio of carbon nanotubes, reduced graphene oxide, Sn, and ZnO in the bottom layer is 40~55:15~30:5~15:10~20; the mass ratio of hard carbon, soft carbon, and conductive carbon black in the intermediate layer is 80~90:5~10:1~3; and the mass ratio of porous hard carbon, sodium superionic conductor, NaF, and Na3PO4 in the surface layer is 45~70:10~30:2.5~10:2.5~10, or the mass ratio of porous hard carbon, sodium superionic conductor, NaF, and borate film-forming additive is 45~70:10~30:2.5~10:2.5~10.

[0048] In some specific embodiments, the bottom layer, intermediate layer, and top layer further include an adhesive. Optionally or preferably: the adhesive in the bottom layer includes polyvinylidene fluoride (PVDF), comprising 1-15% by mass of the bottom layer; the adhesive in the intermediate layer includes sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), comprising 1-5% by mass of the intermediate layer; the adhesive in the top layer includes an elastic adhesive, comprising 1-15% by mass of the intermediate layer, wherein the elastic adhesive is selected from one or more of polyacrylic elastic adhesives, polyether elastic adhesives, and polyimide elastic adhesives.

[0049] In some specific embodiments, the thickness of the bottom layer is 0.5~5 μm, the thickness of the intermediate layer is 15~120 μm, the thickness of the top layer is 1~25 μm, and the total thickness of the bottom layer, intermediate layer and top layer is 20~150 μm.

[0050] In some specific embodiments, the porosity of the substrate is 5% to 30%, and the average pore size is 20 to 300 nm.

[0051] In some specific embodiments, the porosity of the intermediate layer is 18% to 38%, and the average pore size is 0.05 to 1.5 μm.

[0052] In some specific embodiments, the porosity of the surface layer is 28% to 55%, and the average pore size is 0.1 to 3.0 μm.

[0053] Second, the present invention relates to the application of the three-layer functionalized negative electrode in a high-power energy storage battery, wherein the high-power energy storage battery is a lithium-ion battery or a sodium-ion battery.

[0054] In some specific embodiments, the high-power energy storage battery includes a positive electrode, a separator, an electrolyte, and the three-layer functionalized negative electrode; the separator is stacked on the surface layer of the three-layer functionalized negative electrode.

[0055] The present invention does not impose any special restrictions on the preparation method of the three-layer functionalized negative electrode, and conventional methods in the art can be used for its preparation.

[0056] The present invention will now be described with reference to specific embodiments and comparative examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0057] Example 1: Negative electrode and lithium-ion battery The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, the structure consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, and PVDF in a mass ratio of 45:25:20:10. The intermediate layer is composed of high-ratio artificial graphite (purchased from BTR New Energy Materials Co., Ltd., model AGP-8H, particle size D50 of 10 μm; the high-ratio artificial graphite used in the following examples and comparative examples is the same) in a mass ratio of 86:8:1.5:0.5:1.5:2.5, silicon-carbon composite material (purchased from Shanshan Technology, model Si / C-450, particle size D50 of 5 μm, core-shell structure, the core layer consisting of a porous carbon matrix and dispersed nano-silicon, the shell layer being amorphous carbon; the silicon-carbon composite material used in the following examples and comparative examples is the same), and conductive carbon black (Super The surface layer consists of porous hard carbon (D50 of 4 μm and D90 of 11 μm; the porous hard carbon used in the following examples and comparative examples is the same) in a mass ratio of 40:25:15:5:15, LLZO, LiF, LiDFOB and polyacrylic elastic binder.

[0058] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is measured to be 2.01 μm, the porosity is 14.5%, and the average pore size is 85 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 62 μm, the porosity is 27.2%, and the average pore size is 0.42 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 8.4 μm, a porosity of 42.0%, and an average pore size of 0.65 μm. S4: After rolling, slitting and drying, the following is obtained: Figure 2 The three-layer functionalized negative electrode shown employs a two-stage rolling process with the following parameters (the rolling parameters in the following examples and comparative examples are the same): the first stage rolling temperature is 40℃, the linear pressure is 50 kN / m, and the roll gap is 100 μm; the second stage rolling temperature is 50℃, the linear pressure is 70 kN / m, and the roll gap is 85 μm; the rolling speed for both stages is 10 m / min; and the rebound stabilization time of the negative electrode after rolling is 24 h.

[0059] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are as follows: The three-layer functionalized anode and lithium iron phosphate cathode (composed of lithium iron phosphate, Super P, carbon nanotubes and PVDF in a mass ratio of 96.0:1.0:1.0:2.0, with an areal density of 230 g / m³) are used. 2 The compacted density is 2.35 g / cm³. 3 The cells are stacked together with a ceramic-coated polyolefin separator (15 μm thick), and an electrolyte (a mixed carbonate solvent consisting of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a volume ratio of 3:5:2, with 1.0 mol / L LiPF6, 2.0 wt% fluoroethylene carbonate, 1.0 wt% LiDFOB and 0.5 wt% LiPO2F2 dissolved in it) is injected. The cells are then vacuum-sealed, left to stand, formed, aged and tested for capacity to obtain a 15 Ah high-power energy storage cell (the cell is designed to have a capacity of 15 Ah and a nominal voltage of 3.2 V). After being assembled with a casing, a lithium-ion battery is obtained.

[0060] Example 2: Negative electrode and lithium-ion battery The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, vapor-grown carbon fibers, TiN, and LiF in a mass ratio of 40:20:25:15. The intermediate layer is composed of high-ratio artificial graphite and silicon-carbon composite material in a mass ratio of 95:5. The top layer is composed of porous hard carbon, LATP, Li3PO4, LiBOB, and polyacrylic acid elastic binder in a mass ratio of 42:24:14:6:14.

[0061] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 1.54 μm, the porosity is 11.9%, and the average pore size is 60 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 58 μm, the porosity is 25.2%, and the average pore size is 0.35 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 6.4 μm, a porosity of 39.5%, and an average pore size of 0.50 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0062] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are the same as in Embodiment 1.

[0063] Example 3: Negative electrode and lithium-ion battery The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, the structure consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of reduced graphene oxide, carbon nanotubes, SnO2, and LiAlO2 in a mass ratio of 35:25:25:15. The intermediate layer is composed of high-ratio artificial graphite, hard carbon (particle size D50 of 5 μm and D90 of 13 μm; the hard carbon used in the following examples and comparative examples is the same) in a mass ratio of 74:10:10:2:1.5:2.5, silicon-oxygen-carbon composite material (purchased from Shanshan Technology, model SiO2). x / C-500, with a particle size D50 of 6 μm, has a core-shell structure, and the core layer is SiO2. x The shell is composed of amorphous carbon, conductive carbon black, CMC and SBR; the surface layer is composed of porous hard carbon, LAGP, LiF, Li3PO4 and polyether elastic binder in a mass ratio of 50:20:8:7:15.

[0064] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is measured to be 2.83 μm, the porosity is 17.3%, and the average pore size is 120 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 75 μm, the porosity is 30.4%, and the average pore size is 0.72 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 12 μm, a porosity of 46.8%, and an average pore size of 0.95 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0065] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are the same as in Embodiment 1.

[0066] Example 4: Negative electrode and lithium-ion battery The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, Ag nanoparticles, and PVDF in a mass ratio of 45:20:20:15. The intermediate layer is composed of high-ratio artificial graphite, lithium titanate, and silicon-carbon composite material in a mass ratio of 81:15:4. The top layer is composed of porous hard carbon, LLZO, LiF, and polyimide elastic binder in a mass ratio of 45:25:15:15.

[0067] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 1.21 μm, the porosity is 9.5%, and the average pore size is 45 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 52 μm, the porosity is 24.7%, and the average pore size is 0.28 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 5.0 μm, a porosity of 36.4%, and an average pore size of 0.35 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0068] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are the same as in Embodiment 1.

[0069] Example 5: Negative electrode and lithium-ion battery The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, and PVDF in a mass ratio of 45:25:20:10. The intermediate layer is composed of high-ratio artificial graphite, silicon-carbon composite material, Super P, carbon nanotubes, CMC, and SBR in a mass ratio of 86:8:1.5:0.5:1.5:2.5. The top layer is composed of porous hard carbon, LLZO, LiF, LiDFOB, and polyacrylic elastic binder in a mass ratio of 40:25:15:5:15.

[0070] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 2.50 μm, the porosity is 18.6%, and the average pore size is 135 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 80 μm, the porosity is 32.2%, and the average pore size is 0.80 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 14 μm, a porosity of 48.0%, and an average pore size of 1.15 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0071] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are the same as in Embodiment 1.

[0072] Example 6: Negative electrode and lithium-ion battery The only difference between this embodiment and Embodiment 4 is that: the Ag nanoparticles in the bottom layer are replaced with ZnO nanoparticles and LiF; the lithium titanate in the middle layer is replaced with hard carbon and carbon nanotubes; and the LLZO in the surface layer is replaced with LLZTO, and some of the LiF is replaced with Li3PO4. Specifically: The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, LiF, and PVDF in a mass ratio of 45:20:15:5:15. The intermediate layer is composed of high-ratio artificial graphite, hard carbon, silicon-carbon composite material, and carbon nanotubes in a mass ratio of 81:14:4:1. The top layer is composed of porous hard carbon, LLZTO, LiF, Li3PO4, and polyimide elastic binder in a mass ratio of 45:25:7.5:7.5:15.

[0073] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 1.25 μm, the porosity is 9.5%, and the average pore size is 48 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 53 μm, the porosity is 24.5%, and the average pore size is 0.30 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 5.2 μm, a porosity of 36.8%, and an average pore size of 0.37 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0074] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are the same as in Embodiment 1.

[0075] Example 7: Negative electrode and lithium-ion battery The only difference between this embodiment and Embodiment 6 is that hard carbon is not used in the intermediate layer. Specifically: The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, LiF, and PVDF in a mass ratio of 45:20:15:5:15. The intermediate layer is composed of high-ratio artificial graphite, silicon-carbon composite material, and carbon nanotubes in a mass ratio of 95:4:1. The top layer is composed of porous hard carbon, LLZTO, LiF, Li3PO4, and polyimide elastic binder in a mass ratio of 45:25:7.5:7.5:15.

[0076] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 1.18 μm, the porosity is 8.8%, and the average pore size is 44 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 51 μm, the porosity is 23.5%, and the average pore size is 0.27 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 4.9 μm, a porosity of 35.6%, and an average pore size of 0.34 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0077] The lithium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are the same as in Embodiment 1.

[0078] Example 8: Negative electrode and sodium-ion battery The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, the structure consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, Sn, and ZnO in a mass ratio of 45:25:15:15. The intermediate layer is composed of hard carbon, soft carbon, Super P, CMC, and SBR in a mass ratio of 88:7:2:1.5:1.5. The top layer is composed of porous hard carbon and NASICON-type sodium ion conductor (Na3Zr2Si2PO4) in a mass ratio of 46:26:10:6:12. 12 It is composed of NaF, NaDFOB and polyacrylic elastic adhesive.

[0079] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is measured to be 2.20 μm, the porosity is 15.1%, and the average pore size is 95 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 68 μm, the porosity is 29.4%, and the average pore size is 0.55 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 10 μm, a porosity of 43.0%, and an average pore size of 0.75 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0080] The sodium-ion battery is prepared using the three-layer functionalized negative electrode of this embodiment, and the steps are as follows: A three-layer functionalized negative electrode, a layered oxide sodium-ion positive electrode, and a ceramic-coated polyolefin separator (15 μm thick) are stacked and assembled. Sodium-ion battery electrolyte (a mixed carbonate solvent consisting of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 3:5:2, with 1.0 mol / L NaPF6, 2.0 wt% fluoroethylene carbonate, 1.0 wt% NaDFOB, and 0.5 wt% NaPO2F2 dissolved) is injected, vacuum-sealed, left to stand, formed, aged, and capacity-balanced to obtain a 15 Ah high-power energy storage cell (cell design capacity of 15 Ah, nominal voltage of 3.0 V). After being assembled with a casing, a sodium-ion battery is obtained.

[0081] Example 9: Negative electrode and sodium-ion battery The only difference between this embodiment and Embodiment 8 is that soft carbon is not used in the intermediate layer. Specifically: The three-layer functionalized negative electrode structure in this embodiment is as follows: Figure 1 As shown, the structure consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, Sn, and ZnO in a mass ratio of 45:25:15:15. The intermediate layer is composed of hard carbon, Super P, CMC, and SBR in a mass ratio of 95:2:1.5:1.5. The top layer is composed of porous hard carbon and NASICON-type sodium ion conductor (Na3Zr2Si2PO4) in a mass ratio of 46:26:10:6:12. 12 It is composed of NaF, NaDFOB and polyacrylic elastic adhesive.

[0082] The three-layer functionalized negative electrode in this embodiment is prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 2.13 μm, the porosity is 14.6%, and the average pore size is 92 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 68 μm, the porosity is 30.2%, and the average pore size is 0.51 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 10 μm, a porosity of 44.5%, and an average pore size of 0.67 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0083] Sodium-ion batteries were prepared using the three-layer functionalized negative electrode of this embodiment, following the same steps as in Example 8.

[0084] Comparative Example 1: Negative Electrode and Lithium-ion Battery The only difference between this comparative example and Example 1 is that this comparative example uses a conventional single-layer graphite anode. Specifically: The monolayer graphite anode of this comparative example consists of a current collector and a graphite layer disposed on the current collector, wherein: the current collector is copper foil; the graphite layer is composed of high-ratio artificial graphite, Super P, CMC and SBR in a mass ratio of 95.5:1.5:1.5:1.5.

[0085] The monolayer graphite anode of this comparative example was prepared through the following steps: S1: All components of the graphite layer are dispersed in water to form a bottom slurry, which is then coated onto the surface of the current collector. After drying and rolling, a graphite layer is formed. The thickness of the graphite layer is 68 μm, the porosity is 27%, and the average pore size is 0.45 μm. S2: After slitting and drying, a single-layer graphite anode is obtained.

[0086] A lithium-ion battery was prepared using the monolayer graphite anode of this comparative example, following the same steps as in Example 1.

[0087] Comparative Example 2: Negative Electrode and Lithium-ion Battery The only difference between this comparative example and Example 1 is that the negative electrode does not contain the bottom layer as in Example 1, but only the intermediate layer and surface layer as in Example 1. Specifically: The bilayer functionalized negative electrode of this comparative example consists of a current collector and an inner layer and a surface layer sequentially disposed on the current collector. The current collector is copper foil. The inner layer is composed of high-ratio artificial graphite, silicon-carbon composite material, Super P, carbon nanotubes, CMC and SBR in a mass ratio of 86:8:1.5:0.5:1.5:2.5. The surface layer is composed of porous hard carbon, LLZO, LiF, LiDFOB and polyacrylic elastic binder in a mass ratio of 40:25:15:5:15.

[0088] The bilayer functionalized anode of this comparative example was prepared through the following steps: S1: All components of the inner layer are dispersed in water to form an inner layer slurry, which is then coated onto the surface of the current collector and dried to form the inner layer. The inner layer is measured to have a thickness of 61 μm, a porosity of 26.5%, and an average pore size of 0.40 μm. S2: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the inner surface and dried to form the surface layer. The surface layer is measured to have a thickness of 8.2 μm, a porosity of 41.5%, and an average pore size of 0.63 μm. S3: After rolling, slitting and drying, a double-layer functionalized negative electrode is obtained.

[0089] A lithium-ion battery was prepared using the bilayer functionalized negative electrode of this comparative example, following the same steps as in Example 1.

[0090] Comparative Example 3: Negative Electrode and Lithium-ion Battery The only difference between this comparative example and Example 1 is that the negative electrode does not have the surface layer as in Example 1, but only the bottom layer and intermediate layer as in Example 1. Specifically: The bilayer functionalized negative electrode of this comparative example consists of a current collector and a bottom layer and an outer layer sequentially disposed on the current collector. The current collector is copper foil; the bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles and PVDF in a mass ratio of 45:25:20:10; the outer layer is composed of high-ratio artificial graphite, silicon-carbon composite material, Super P, carbon nanotubes, CMC and SBR in a mass ratio of 86:8:1.5:0.5:1.5:2.5.

[0091] The bilayer functionalized anode of this comparative example was prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is measured to be 2.1 μm, the porosity is 14.5%, and the average pore size is 88 nm. S2: All components of the outer layer are dispersed in water to form an outer layer slurry, which is then coated onto the surface of the bottom layer and dried to form the outer layer. The outer layer is measured to have a thickness of 61.5 μm, a porosity of 26.8%, and an average pore size of 0.41 μm. S3: After rolling, slitting and drying, a double-layer functionalized negative electrode is obtained.

[0092] A lithium-ion battery was prepared using the bilayer functionalized negative electrode of this comparative example, following the same steps as in Example 1.

[0093] Comparative Example 4: Negative Electrode and Lithium-ion Battery The only difference between this comparative example and Example 1 is that the porosity and pore size of the surface layer are increased. Specifically: The three-layer functionalized anode structure in this comparative example is as follows: Figure 1As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, and PVDF in a mass ratio of 45:25:20:10. The intermediate layer is composed of high-ratio artificial graphite, silicon-carbon composite material, Super P, carbon nanotubes, CMC, and SBR in a mass ratio of 86:8:1.5:0.5:1.5:2.5. The top layer is composed of porous hard carbon, LLZO, LiF, LiDFOB, and polyacrylic elastic binder in a mass ratio of 40:25:15:5:15.

[0094] The three-layer functionalized anode of this comparative example was prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is measured to be 2.05 μm, the porosity is 14.2%, and the average pore size is 86 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 62.5 μm, the porosity is 27.4%, and the average pore size is 0.43 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 12 μm, a porosity of 62%, and an average pore size of 3.8 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0095] A lithium-ion battery was prepared using the three-layer functionalized negative electrode of this comparative example, following the same steps as in Example 1.

[0096] Comparative Example 5: Negative Electrode and Lithium-ion Battery The only difference between this comparative example and Example 1 is that the porosity and pore size of the surface layer are reduced. Specifically: The three-layer functionalized anode structure in this comparative example is as follows: Figure 1 As shown, it consists of a current collector 1 and a bottom layer 2, an intermediate layer 3, and a top layer 4 sequentially disposed on the current collector. The current collector is copper foil. The bottom layer is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, and PVDF in a mass ratio of 45:25:20:10. The intermediate layer is composed of high-ratio artificial graphite, silicon-carbon composite material, Super P, carbon nanotubes, CMC, and SBR in a mass ratio of 86:8:1.5:0.5:1.5:2.5. The top layer is composed of porous hard carbon, LLZO, LiF, LiDFOB, and polyacrylic elastic binder in a mass ratio of 40:25:15:5:15.

[0097] The three-layer functionalized anode of this comparative example was prepared through the following steps: S1: All components of the bottom layer are dispersed in water to form a bottom layer slurry, which is then coated onto the surface of the current collector and dried to form the bottom layer. The thickness of the bottom layer is 1.95 μm, the porosity is 13.7%, and the average pore size is 83 nm. S2: All components of the intermediate layer are dispersed in water to form an intermediate layer slurry, which is then coated onto the surface of the bottom layer and dried to form the intermediate layer. The thickness of the intermediate layer is measured to be 61.8 μm, the porosity is 26.7%, and the average pore size is 0.41 μm. S3: All components of the surface layer are dispersed in water to form a surface slurry, which is then coated onto the surface of the intermediate layer and dried to form the surface layer. The surface layer is measured to have a thickness of 8 μm, a porosity of 22%, and an average pore size of 0.06 μm. S4: After rolling, slitting and drying, a three-layer functionalized negative electrode is obtained.

[0098] A lithium-ion battery was prepared using the three-layer functionalized negative electrode of this comparative example, following the same steps as in Example 1.

[0099] Comparative Example 6: Negative Electrode and Lithium-ion Battery The only difference between this comparative example and Example 1 is that the components used in the bottom layer, intermediate layer, and top layer are mixed in the same layer (the amount of each component is the same as in Example 1). Specifically: The single-layer negative electrode of this comparative example consists of a current collector and a surface coating disposed on the current collector, wherein: the current collector is copper foil; the surface coating is composed of carbon nanotubes, reduced graphene oxide, ZnO nanoparticles, PVDF, high-ratio artificial graphite, silicon-carbon composite material, Super P, carbon nanotubes, CMC, SBR, porous hard carbon, LLZO, LiF, LiDFOB and polyacrylic elastic binder, and the amounts of these components are the same as in Example 1.

[0100] The monolayer anode of this comparative example was prepared by the following steps: S1: All components of the surface coating are dispersed in water to form a coating slurry, which is then coated onto the surface of the current collector. After drying and rolling, a surface coating is formed. The thickness of the surface coating is measured to be 72 μm, the overall porosity is 31%, and the average pore size is 0.85 μm. S2: After slitting and drying, a single-layer negative electrode is obtained.

[0101] A lithium-ion battery was prepared using the single-layer negative electrode of this comparative example, following the same steps as in Example 1.

[0102] Test case The battery cells from each embodiment and comparative example were subjected to performance tests. The test items are as follows: 0.5C discharge capacity, 1kHz AC internal resistance, 10s DC internal resistance, 5C continuous discharge capacity retention rate, voltage drop after 10s of 10C pulse discharge, capacity retention rate after 3000 cycles of 3C charge / 3C discharge, and the highest temperature rise of the battery cell at 5C discharge in an environment of 25℃. The 5C continuous discharge capacity retention rate was calculated based on the discharge capacity measured at 0.2C rate for the same battery cell. The test results are shown in Table 1.

[0103] Table 1. Cell performance test results

[0104] Test Result Analysis: (1) Compared to conventional single-layer graphite anodes (Comparative Example 1), when using the three-layer functionalized anodes in Examples 1-8, the internal resistance of the lithium-ion battery cell, the voltage drop during 10C pulse discharge, and the maximum temperature rise during 5C discharge are lower, while the capacity retention rate during 5C continuous discharge and the capacity retention rate during 3C charge-discharge cycles are higher. This indicates that the three-layer functionalized anode of the present invention can effectively reduce the internal resistance of lithium-ion batteries and improve their rate performance, cycle life, and safety stability. Furthermore, Figure 3 The voltage response of the cells of Example 1 and Comparative Example 1 under 5C pulse discharge is shown. It is shown that the voltage drop of the cell of Example 1 after 10s of discharge is significantly smaller than that of Comparative Example 1, which is consistent with the situation under 10C pulse discharge. Figure 4 The capacity changes of the cells from Example 1 and Comparative Example 1 during 0-3000 cycles at 3C / 3C high rate are shown. It is evident that the capacity decrease rate of the cell from Example 1 is significantly lower than that of Comparative Example 1 as the number of cycles increases. Furthermore, after 3000 cycles of 3C charge / 3C discharge, disassembly of the cell from Comparative Example 1 revealed significant localized SEI thickening on the negative electrode separator side, with slight lithium plating traces in some areas. Examples 1-8 did not exhibit these phenomena, demonstrating the superior cycle life of Examples 1-8. The cells from Examples 1-8 did not ignite or explode after nail penetration testing and being held in a 130°C hot box for 30 minutes, indicating that the lithium-ion battery exhibits high safety and stability when using the three-layer functionalized negative electrode of this invention.

[0105] (2) Compared with Comparative Examples 2 and 3, the cell internal resistance of Example 1 has a lower 10C pulse discharge voltage drop and a lower maximum temperature rise during 5C discharge, while the 5C continuous discharge capacity retention rate and 3C charge-discharge cycle capacity retention rate are higher. The reason for this is that in the three-layer functionalized negative electrode of the present invention, the bottom layer is responsible for conducting electricity and promoting the nucleation of working ions. It can move the electron transport backbone forward to the surface of the current collector and make the working ions nucleate uniformly near the current collector side, which can reduce the difference in in-plane current distribution and suppress local lithium / sodium plating on the current collector side and the increase in contact resistance. The top layer is responsible for ion flux homogenization and SEI film stabilization. It can buffer and homogenize the ion flow entering the negative electrode. At the same time, the solid fast ion conductor and SEI film precursor help to form a stable interface on the surface of the negative electrode, which can reduce repeated SEI film rupture, dead lithium / dead sodium generation and high-temperature side reactions. Therefore, when the top or bottom layer is missing, the battery internal resistance will increase, and the rate performance, cycle life and safety stability will decrease.

[0106] (3) Although the negative electrode of Comparative Example 6 contains the same functional components as in Example 1, the components are randomly dispersed and do not form an ordered functional partition structure of “conductive-working ion nucleation layer → high-capacity fast lithium storage layer → ion flux regulation-stable SEI layer” along the thickness direction. As a result, the improvement effect of these functional components on the cell internal resistance, rate performance, cycle life and safety stability is significantly worse than that of Example 1.

[0107] (4) Compared with Comparative Example 4 and Comparative Example 5, the cell internal resistance of Example 1 has a lower voltage drop during 10C pulse discharge and a lower maximum temperature rise during 5C discharge. The capacity retention rate during 5C continuous discharge and the capacity retention rate during 3C charge-discharge cycles are higher. Furthermore, after disassembling the cell after 3000 3C charge / 3C discharge cycles, it was found that the local channel collapse and non-uniform thickening of the SEI on the surface of the negative electrode of Comparative Example 4 were more obvious, while the above phenomena did not appear in Example 1. The reasons are as follows: In Comparative Example 4, the porosity and average pore size of the negative electrode surface layer are too large, making it easy for ions to quickly pass through the surface layer to reach the intermediate layer surface, making it difficult for them to be evenly distributed within the surface layer. At the same time, the excessively large pore size will also introduce bubbles and metastable states caused by lean electrolyte retention. Trace amounts of gas generated during high-power cycling or high-temperature storage are more likely to be retained and merged in the large pores, forming local insulating gas plugs. The liquid phase pathway near the gas plugs is forced to flow around, further leading to uneven ion flux. In addition, it will also cause uneven interfacial reactions. In Comparative Example 5, the porosity and average pore size of the negative electrode surface layer are too small, which will cause electrolyte wetting and ion diffusion to be hindered, and concentration polarization will increase under high-rate conditions.

[0108] (5) Compared with Example 1, the high-rate polarization and cycle decay of the cell in Example 5 are slightly increased, indicating that within a certain range, when the porosity and average pore size in the bottom layer, middle layer and surface layer are increased, the tendency of local liquid phase bypass and interface inhomogeneity begins to increase.

[0109] (6) Compared with Examples 4 and 7, the internal resistance of the cell in Example 6 is lower. The reason for this is that in the negative electrode bottom layer of Example 6, ZnO and LiF are distributed on a quasi-continuous electronic equipotential surface composed of carbon nanotubes and reduced graphene oxide. This can transform the local lithium intercalation reaction near the current collector side of the intermediate layer from point nucleation to strip or planar nucleation, thereby improving the interfacial bonding between the bottom layer and the intermediate layer and improving the transport stability at the interface. Compared with Example 4, which only uses Ag nanoparticles as the bottom nucleation regulating component, although Ag has better lithium affinity and conductivity, it is easier to form discrete metal nucleation points. It is difficult to provide the synergistic effect of ZnO polar sites and LiF point mechanical framework at the same time. Therefore, it is relatively inferior to the ZnO / LiF composite system in terms of interfacial bonding, nucleation expansion and long-term transport stability. In the negative electrode intermediate layer of Example 6, hard carbon can fill the curvature gaps between graphite flake particles and form a wider lithium-ion inlet. Carbon nanotubes can penetrate through the thickness direction of the intermediate layer and overlap with the bottom carbon nanotube-reduced graphene oxide network. This means that electron transport from the bottom layer to the intermediate layer is not simply a vertical passage through the interface, but rather a repeated diversion along the graphite flakes, hard carbon, silicon-carbon composite material and carbon nanotubes, thereby improving the electron transport efficiency and electron transport stability at the interface.

[0110] (7) Compared with Example 8, Example 9 showed a slight increase in cell internal resistance, 10C pulse discharge voltage drop, and 5C discharge maximum temperature rise, while a slight decrease in 5C continuous discharge capacity retention and 3C charge-discharge cycle capacity retention. The reason for this is that the intermediate layer of Example 8 simultaneously contains hard carbon, soft carbon, and conductive carbon black. Hard carbon provides the main sodium storage sites, soft carbon can form a relatively continuous electron transport phase and flexible contact phase between hard carbon particles, and conductive carbon black further fills the micropores between particles and reduces local contact impedance. However, Example 9 did not use soft carbon, and the intermediate layer mainly relied on hard carbon and conductive carbon black to form a conductive network. The continuity of the electron shunting path, the stability of inter-particle contact, and the stress buffering capacity during cycling were slightly weaker. Therefore, Example 9 can still achieve better high-rate performance through the sodium-loving nucleation regulation effect of Sn / ZnO in the bottom layer and the ion flux homogenization and SEI stabilization effect of NASICON / NaF / NaDFOB in the surface layer, but its overall performance is lower than that of Example 8. This result further illustrates that the combination of hard carbon, soft carbon, and conductive carbon black in the intermediate layer is beneficial to improving the high-power cycle stability of sodium-ion batteries.

Claims

1. A three-layer functionalized lithium-ion battery negative electrode, characterized in that, The device includes a current collector, on which a bottom layer, an intermediate layer, and a top layer are sequentially arranged. The bottom layer contains carbon nanotubes, reduced graphene oxide, ZnO, and LiF. The intermediate layer contains graphite, hard carbon, silicon-carbon composite material, and carbon nanotubes. The top layer contains porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF, and Li3PO4. The porosity of the bottom layer is 5% to 30%, and the average pore size is 20 to 300 nm. The porosity of the intermediate layer is 18% to 38%, and the average pore size is 0.05 to 1.5 μm. The porosity of the top layer is 28% to 55%, and the average pore size is 0.1 to 3.0 μm.

2. The three-layer functionalized lithium-ion battery negative electrode according to claim 1, characterized in that, In the bottom layer, the mass ratio of carbon nanotubes, reduced graphene oxide, ZnO, and LiF is 40~55:15~30:10~20:5~15; in the middle layer, the mass ratio of graphite, hard carbon, silicon-carbon composite material, and carbon nanotubes is 78~92:5~14:3~8:0.2~1.0; in the top layer, the mass ratio of porous hard carbon, tantalum-doped lithium lanthanum zirconium oxide, LiF, and Li3PO4 is 45~70:10~30:2.5~10:2.5~10.

3. The three-layer functionalized lithium-ion battery negative electrode according to claim 1, characterized in that, The thickness of the bottom layer is 0.5~5 μm, the thickness of the middle layer is 15~120 μm, and the thickness of the top layer is 1~25 μm.

4. The three-layer functionalized lithium-ion battery negative electrode according to claim 1 or 3, characterized in that, The total thickness of the bottom layer, intermediate layer and top layer is 20~150 μm.

5. A three-layer functionalized sodium-ion battery negative electrode, characterized in that, The device includes a current collector, on which layers are formed: a bottom layer, an intermediate layer, and a top layer. The bottom layer contains carbon nanotubes, reduced graphene oxide, Sn, and ZnO. The intermediate layer contains hard carbon, soft carbon, and conductive carbon black. The top layer contains porous hard carbon, sodium superionic conductor, and NaF, and contains Na3PO4 and / or borate film-forming additives. The bottom layer has a porosity of 5% to 30% and an average pore size of 20 to 300 nm. The intermediate layer has a porosity of 18% to 38% and an average pore size of 0.05 to 1.5 μm. The top layer has a porosity of 28% to 55% and an average pore size of 0.1 to 3.0 μm.

6. The three-layer functionalized sodium-ion battery negative electrode according to claim 5, characterized in that, In the bottom layer, the mass ratio of carbon nanotubes, reduced graphene oxide, Sn, and ZnO is 40~55:15~30:5~15:10~20; in the middle layer, the mass ratio of hard carbon, soft carbon, and conductive carbon black is 80~90:5~10:1~3; in the surface layer, the mass ratio of porous hard carbon, sodium superionic conductor, NaF, and Na3PO4 is 45~70:10~30:2.5~10:2.5~10 or the mass ratio of porous hard carbon, sodium superionic conductor, NaF, and borate film-forming additive is 45~70:10~30:2.5~10:2.5~10.

7. The three-layer functionalized sodium-ion battery negative electrode according to claim 5, characterized in that, The thickness of the bottom layer is 0.5~5 μm, the thickness of the middle layer is 15~120 μm, and the thickness of the top layer is 1~25 μm.

8. The three-layer functionalized sodium-ion battery negative electrode according to claim 5 or 7, characterized in that, The total thickness of the bottom layer, intermediate layer and top layer is 20~150 μm.

9. The application of the three-layer functionalized lithium-ion battery negative electrode according to any one of claims 1 to 4 in a high-power energy storage battery, characterized in that, The high-power energy storage battery is a lithium-ion battery.

10. The application of the three-layer functionalized sodium-ion battery negative electrode according to any one of claims 5 to 8 in a high-power energy storage battery, characterized in that, The high-power energy storage battery is a sodium-ion battery.

Citation Information

Patent Citations

  • Modified graphite negative electrode material and preparation method thereof, negative electrode and lithium ion battery

    CN122000333A

  • Sodium-ion battery composite negative electrode, battery and preparation method of negative electrode

    CN116825962A

  • Metal lithium negative electrode and preparation method thereof

    CN118099366A